Preface - Garrido, Paulo (2017)
[Excerpt] The biennial CONTROLO conferences are the main events promoted by the Portu-guese Association for Automatic Control – APCA, national member organization of the International Federation of Automatic Control – IFAC. The CONTROLO 2016 – 12th Portuguese Conference on Automatic Control, Guimarães, Portugal, September 14th to 16th, was organized by Algoritmi, School of Engineering, University of Minho, in partnership with INESC TEC. This edition of the conference has been approved for co-sponsorship by IFAC. The conference had three partners: CEA – Comité Español de Automática, SPEE – the Portuguese Association for Education Engineering, and SPR – the Portuguese Association for Robotics. [...]